GERAKAN LITERASI SEKOLAH SMA NEGERI 10 PALEMBANG - Indani, Nur (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The School Literacy Movement strengthens the movement of growth in character as outlined in the Minister of Education and Culture Regulation No. 23 of 2015. One of the activities in the movement is "15 Minute Activities to Read Non-Learning Books Before Learning Time Begins". This routine activity is carried out to foster interest in reading students / students as well as in order to improve reading skills so that knowledge can be mastered better. The reading material contains the values of character, in the form of local, national, and global wisdom delivered according to the development stage of the students. This study wanted to see "The extent to which the School Literacy Movement Can Cultivate a Culture of Reading among Palembang State High School Students. Literacy activities develop oral culture. Strong literacy-based class is expected to bring up various oral activities in the form of discussions about books during classroom learning. This discussion activity also needs to open up possibilities for differences of opinion so that critical thinking skills can be honed. Learners need to learn to convey their feelings and opinions, listen to each other, and respect different views. This school literacy habit aims to foster reading interest in reading and for reading activities in school residents. The growth of reading interest is fundamental to the development of students' literacy skills.